2015
DOI: 10.1590/0366-69132015613601932
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and antibacterial properties of yttriumdoped ZnO nanoparticles

Abstract: Yttrium-doped ZnO nanoparticles were synthesized by co-precipitation method to investigate structural, optical and antibacterial properties. X-ray diffraction analysis confirms hexagonal (wurtzite) structure with average crystallite size between 16 and 30 nm. Optical energy band gap decreaseswith increasing Y-doping concentration. ZnO nanoparticles were found to be highly effective against S. aureus and Y-doped ZnO nanoparticles against E. coli, B. subtilis and S. typhi. Undoped and Y-doped ZnO nanoparticles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…4), according to the methodology described by [15], and the observed values were 3.2 eV for pure ZnO and 2.9 eV for ZNAL. Similar results were obtained by Bel-HadjTahar and Mohamed [25], who observed a decrease in the band gap value when ZnO was doped with aluminum, and Mote et al [26], who observed a decrease in the band gap value when ZnO was doped with yttrium. Bai et al [23] evaluated the influence of Al-doping into ZnO by firstprinciple calculations.…”
Section: Catalyst Characterizationsupporting
confidence: 88%
“…4), according to the methodology described by [15], and the observed values were 3.2 eV for pure ZnO and 2.9 eV for ZNAL. Similar results were obtained by Bel-HadjTahar and Mohamed [25], who observed a decrease in the band gap value when ZnO was doped with aluminum, and Mote et al [26], who observed a decrease in the band gap value when ZnO was doped with yttrium. Bai et al [23] evaluated the influence of Al-doping into ZnO by firstprinciple calculations.…”
Section: Catalyst Characterizationsupporting
confidence: 88%
“…Yttrium-doped ZnO-NPs were utilized as antimicrobial agents against B. subtilis, S. typhi and E. coli. Pure ZnO-NPs showed excellent antimicrobial efficacy against S. aureus while ZnO-NPs doped with Yttrium showed excellent inhibition for all the tested strains 35 . Hence, Y-doped ZnO-NPs can serve as inexpensive and good inorganic antimicrobial agents.…”
Section: A Baumanniimentioning
confidence: 98%
“…46 The optical band gap value was 2.7 eV, which was supported by a literature review. 3 The proposed mechanism pathway for the degradation of MO in the presence of the nanocatalyst and sunlight is shown in Figure 7.…”
Section: T H Imentioning
confidence: 99%
“…Some of the progressive areas of green chemistry are the solvent-free and microwave conditions used for various types of organic reactions with nanocatalysts as heterogeneous catalysts. Metal oxides and, particularly, bimetallic oxide nanoparticles have several applications including as catalysts, photocatalysts, antimicrobial agents, materials with magnetic properties, and CT-DNA binding agents . The most attractive feature of nanoparticles lies in the field of green chemistry as they serve as green catalysts in organic reactions and have advantages such as easy separation from the reaction mixture by simple filtration, reusability, recyclability, and environmental friendliness. , …”
Section: Introductionmentioning
confidence: 99%